Acceptance and resistance of eWallet adoption: an integrated theoretical exploration in dynamic socio-economic environments - Tan, Mui Lim (2025)
EWallet, as a form of mobile wallet has emerged as a disruptive innovation in various industries. It has gained significant attention and adoption during the COVID-19 pandemic where the pandemic created a need for contactless payment methods to reduce the risk of virus transmission through physical banknotes (Undale et al., 2021). Hence, eWallet has the potential to serve as a crisis management tool due to its convenience and accessibility. It presented a notable shift towards digital transactions and a reduction of physical cash reliance, moving to a cashless economy. Therefore, this research aims to capture the eWallet adoption in response to crises, their limitations, and barriers to their adoption in promoting its sustainability usage.